ANGGARAN KAS SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN KEUANGAN PERUSAHAAN - Siti Reskiyawati Said (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Cash budget is an essential component of financial planning that enables companies to estimate future cash inflows and cash outflows within a specific period. Effective cash budgeting plays a significant role in maintaining liquidity, ensuring operational continuity, and supporting strategic financial decision-making. This study aims to examine the concept, objectives, importance, and preparation format of cash budgets in corporate financial management. The research employs a qualitative approach using a literature review method by analyzing various books, academic journals, and relevant references related to budgeting and financial management. The findings indicate that cash budgeting serves not only as a planning tool but also as a mechanism for controlling cash flows and evaluating financial performance. Through cash budgeting, companies can anticipate potential cash shortages or surpluses, improve the efficiency of cash utilization, and minimize financial risks arising from poor cash management. Furthermore, a well-structured cash budget provides management with accurate information to support decisions regarding financing, investment, and operational activities. Therefore, cash budgeting is a critical instrument in achieving financial stability, enhancing managerial effectiveness, and ensuring the long-term sustainability of business operations.